Fregean Side-Thoughts. Issue 3 (3rd July 2021) - Sander, Thorsten
ABSTRACT: This paper offers a detailed reconstruction of Frege's theory of side-thoughts ( Nebengedanken ) and its relation to other parts of his pragmatics, most notably to the notion of colouring ( Färbung ), to the notion of presupposition ( Voraussetzung ), and to his implicit notion of multi-propositionality. I also highlight some important differences between the subsemantic categories employed by Frege and those used in contemporary pragmatics.